Analisis Kepuasan Pelanggan PT. Sucofindo Melalui Kualitas Layanan, dan Citra Perusahaan - Feliks Anggia Binsar K Panjaitan (Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract: Related business activities performed by PT. Sucofindo, which should consider the satisfaction for customers, thus this research, wish to find out what are the company should do, and also what matters are the customers expect, so that PT. Sucofindo can increase its performance as good as possible.The population was all customers of PT. Sucofindo. The estimation used was Maximum Likelihood Estimation (ML), and sample number would be researched was as large as 100. Data analysis result, indicated values from GFI, AGFI, TLI, CFI, RMSEA and CMIN/DF of 0.931, 0.877, 0.996, 0.997, 0.023 and 1.052, respectively, which all of those in the expected value range.The result of research indicated that: 1. Service quality is influential on image. 2. Service quality is influential on customer satisfaction. 3. Company image is influential on customer satisfaction. 4. Service quality is influential on customer satisfaction, indirectly via company image.Key Words: Service quality, company image, customer satisfaction